EKOLINGUISTIK: MODEL ANALISIS DAN PENERAPANNYA - Subiyanto, Agus (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT Integration includes the meaning of the formation of groups united by a common issue, whether ideological, economic, and social. The overture of national integration movement through the following article tends to create an awareness and a social form that cause many groups with each identity see themselves as one unity: the Indonesian Nation. To create an association in national integration formation, identity has double functions. In addition, the following article is trying to discuss about the challenges for Indonesia to develop the concept of national integration in order to deal with the concept of ethnocentrism, religiousism , and politicalism. Keywords: national integration, ethnocentrism and conflict of interest